A new cave-dwelling species of the genus Geophilus Leach, 1814 (Chilopoda: Geophilomorpha) from the chemoautotrophic-based Movile Cave (Southern Dobrogea, Romania) - Ş. C. Baba; A. Giurginca; G. Popovici; S. M. Sarbu; O. P. Popa (The European Zoological Journal, 2024)
Geophilus zagreus sp. nov., a troglomorphic geophilid endemic to the Movile Cave sulfidic groundwater ecosystem, is described and illustrated. It is distinguished from other European Geophilus species by a high number of coxal pores on the ventral side of the coxa of the last pair of legs. Its affinities with the other two troglobitic species of the genus are discussed. The mitochondrial COI barcode is sequenced for the new species and phylogenetic analysis is carried out to elucidate its placement within Geophilus. Other syntopic Chilopoda from Movile cave are listed.https://www.zoobank.org/urn:lsid:zoobank.org:act:D549ACAF-5DE4-403E-8D1A-5E6232A635E7